The correlation between vitamin D and the occurrence of peripheral neuropathy induced by paclitaxel chemotherapy - Zhang, Jialei; Zhang, Xiaoling; Wu, Jie (Frontiers in Medicine, 2024)
Approximately 80% of cancer patients undergoing Paclitaxel chemotherapy suffer from Paclitaxel-induced peripheral neuropathy (PIPN). The exact mechanisms of PIPN development due to the neurotoxic effects of Paclitaxel are not well understood. Research indicates that the induction and maintenance of chronic pain are associated with peripheral and central neural sensitization, as well as neuroinflammation mediated by inflammatory mediators and chemokines. Persistent pain greatly reduces the quality of life for patients and often leads to dose reduction or cessation of life-saving treatments. In addition to participating in calcium homeostasis and bone metabolism, an increasing number of studies have revealed the role of vitamin D in affecting the body's immune response, regulating brain development, and participating in cognition, as well as regulating cell proliferation and differentiation. The results of several basic and clinical studies show that vitamin D also has an important significance in the perception and regulation of pain. However, there is less research on the correlation between vitamin D and the occurrence and maintenance of PIPN, and more clinical studies are needed to verify whether there is a certain correlation between the two.